2021
DOI: 10.3389/fpubh.2021.740333
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Fear of COVID-19 and Preventive COVID-19 Infection Behaviors Between Iranian and Taiwanese Older People: Early Reaction May Be a Key

Abstract: This study assessed fear of the novel coronavirus-2019 (COVID-19), preventive COVID-19 infection behaviors, and the association between fear of COVID-19 and preventive COVID-19 infection behaviors among older people in Iran and Taiwan. Older people aged over 60 years (n = 144 for Iranians and 139 for Taiwanese) completed the Fear of COVID-19 Scale (FCV-19S) and two items on preventive COVID-19 infection behaviors (i.e., hand washing and mouth covering when sneezing). Iranian older people had a significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 41 publications
3
45
0
Order By: Relevance
“…More specifically, this involved the government's swift activation of the Central Epidemics Command Center, transparent and open communication regarding COVID-19, short-term measures taken to curtail the spread, and measures introduced to lessen the challenges its citizens may go through. 31 Therefore, Taiwanese citizens did not just receive correct and timely information but also received supportive and encouraging messages, substantially lessening their fear and anxiety. In return, Taiwanese citizens understood the need to accommodate these difficult changes and complied with the COVID-19 policies resulting in comparatively lower cases than other countries.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, this involved the government's swift activation of the Central Epidemics Command Center, transparent and open communication regarding COVID-19, short-term measures taken to curtail the spread, and measures introduced to lessen the challenges its citizens may go through. 31 Therefore, Taiwanese citizens did not just receive correct and timely information but also received supportive and encouraging messages, substantially lessening their fear and anxiety. In return, Taiwanese citizens understood the need to accommodate these difficult changes and complied with the COVID-19 policies resulting in comparatively lower cases than other countries.…”
Section: Introductionmentioning
confidence: 99%
“…In order to respond to these needs, several teams have developed different psychometric scales to understand various psychological responses during the COVID-19 outbreak. 3,[20][21][22][23] Additionally, the factors related to the fear of COVID-19 have also been studied. 18,19 For example, one study found that receiving accurate health information and adopting hygiene strategies (eg, handwashing) were associated with lower psychological stress during the COVID-19 epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…The unprecedented situation caused by the SARS-CoV-2 virus has affected each individual’s daily life and well-being in different ways. It has turned out to be particularly difficult for older people and middle-aged adults [ 9 , 10 ]. However, although younger people are at lower risk of severe COVID-19, and there is a lower risk of COVID-19-related complications in this group [ 11 ], they also experience a number of negative consequences of the pandemic.…”
Section: Introductionmentioning
confidence: 99%